The Level of Having Supra-Cognitive Thinking for Law Students at Prince Mohammad Bin Fahd University Based on Some Variables from Their Own Perspective - Hassan, Samia Awad Mohamed; Kherallah, Mona Abdullatif Alawed; Fakhrou, Abbulnaser A. (Advances in Social Sciences Research Journal, 2021)
The objective of this study is to know the level of possessing supra-cognitive thinking skills for the students of the Faculty of Law at Prince Mohammed Bin Fahd University from their own point of view according to some demographic variables. The study followed the descriptive approach, and applied the study tool to a randomly selected sample of (500) students (102) male students, and (398) female students. The results of the study showed that: the study sample members sometimes agree that the law students possess three of the supra-cognitive thinking skills. The study also revealed that there are no statistically significant differences at the level of statistical index of (0.05) or less in the study sample selections about (supra-cognitive thinking skills) based on gender variable. While there are statistically significant differences at the level of statistical index of (0.05) or less, in the replies of the study sample about (supra -cognitive thinking skills) based on the difference of the variable of the study level.